Impact of multiple disturbances and stress on the temporal trajectories and resilience of benthic intertidal communities. Issue 10 (11th October 2018) - Cimon, Stéphanie; Cusson, Mathieu
Abstract: Coastal ecosystems face severe environmental change and anthropogenic pressures that affect both the structure and functioning of communities. Understanding the response and resilience of communities that face multiple simultaneous disturbances and stresses becomes essential. We observed the recovery of a rocky intertidal subarctic macrobenthic community dominated by a macroalgal canopy ( Fucus spp.), a habitat‐forming species, over a period of 14 months. Using 0.25‐m 2 plots, we ran an in situ one‐pulse experiment (removal of all materials to bare rock and then burning of the surface) followed by a full orthogonal factorial design of three press‐type disturbances or stresses: grazer reduction, canopy removal, and nutrient enrichment. We evaluated the single and interactive effects of the three disturbances and stresses on species diversity and abundance structure. Of all the main effects, canopy removal has the most severe impact, resulting in decreased biomass, richness, and diversity, as well as an altered community structure. Canopy‐removed plots had fewer invertebrates and more ephemeral algae; beyond this, however, there was minimal effect from grazer reduction and nutrient enrichment acting individually. We categorized the interaction types of all significant interaction effects: Canopy removal had a dominant effect over grazer reduction on richness, and it also dominated over nutrient enrichment on diversity and evenness. Nutrient enrichment and canopy removal had a negative synergistic interaction effect on richness at the end of the experiment. Without stressors, 11 months were required to achieve full recovery. The three stressors affected recovery time differently, depending on the identity and the number of stressors. Three stressors generally increased the time of recovery or even prevented recovery from being fully attained. Moreover, community structure and composition of plots subjected to the triple‐stressor treatment had not fully recovered by the end of the study. Our results suggest that multiple stressors may interact on community indices and structure and that their interaction cannot be predicted from the outcome of single stressor studies. The inclusion of multiple disturbances and stresses in field experiments provides a better understanding of the mechanisms that shape community structure and their functioning following various forms of disturbance.